2017
DOI: 10.25125/agriculture-journal-ijoear-sep-2017-17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of teat end hyperkeratosis in lactating dairy cattle and their association with animal variables

Abstract: Short and long-term changes in teat condition mainly caused by machine milking may affect the udder health of lactating dairy cattle. The objective was to investigate the prevalence of teat end hyperkeratosis scores in lactating dairy cattle in Germany and to determine associations between animal variables and teat end hyperkeratosis. The study was conducted in 15 German high-yielding dairy herds. On dairy farms teat size, teat shape, teat end shape and changes in teat condition (edema, teat skin colour, teat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…On the contrary, activated keratinocytes have different proteins (K6, K16) in their suprabasal layer associated with hyperproliferation and receptors for infiltrated immune cells. Research suggests that the risk of development of hyperkeratosis increases with lactation number, more days in milk, and teat end shape and size (Neijenhuis et al, 2000;Haverkamp et al, 2017). In both studies the most frequent teat end shape was round, however, the hyperkeratosis score regarding teat end shape differed.…”
Section: Influence Of Machine Milking On Teat Conditionmentioning
confidence: 78%
See 1 more Smart Citation
“…On the contrary, activated keratinocytes have different proteins (K6, K16) in their suprabasal layer associated with hyperproliferation and receptors for infiltrated immune cells. Research suggests that the risk of development of hyperkeratosis increases with lactation number, more days in milk, and teat end shape and size (Neijenhuis et al, 2000;Haverkamp et al, 2017). In both studies the most frequent teat end shape was round, however, the hyperkeratosis score regarding teat end shape differed.…”
Section: Influence Of Machine Milking On Teat Conditionmentioning
confidence: 78%
“…In both studies the most frequent teat end shape was round, however, the hyperkeratosis score regarding teat end shape differed. Haverkamp et al (2017) showed a higher hyperkeratosis score with round teat end, while Neijenhuis et al (2000) suggest that pointed teats are more likely to develop hyperkeratosis. A possible explanation for the different observations may lie in different breeds or milking machine settings.…”
Section: Influence Of Machine Milking On Teat Conditionmentioning
confidence: 96%
“…Every single teat was assessed regarding shape of the entire teat (normal versus others), teat end (normal versus others), height above the ankle (higher versus same height versus lower), length and diameter one centimetre above the apex. The reference values for the teat length and teat diameter were those recorded by Haverkamp et al [26]. Teat injuries were also noted.…”
Section: Examination Of the Uddermentioning
confidence: 86%